Influence of NPK Fertilization on Physiology of Rose - Priya Biswas; Sangita Mahanta; Kankana Deka; Bikash Hazarika; Bhaskarjyoti Sarma (Archives of Current Research International, 2025)
The current study was carried out to assess the influence of different concentrations of nitrogen (N), phosphorus (P), and potassium (K) and their interaction on important physiological parameters—chlorophyll content, stability index of chlorophyll (CSI), and leaf area duration (LAD)—of rose (Rosa spp.) cv. ’Top Secret’ under polyhouse conditions. The experiment was laid out in a factorial randomized block design with three replications at the Experimental Farm, Assam Agricultural University, Jorhat during 2022–2023. Treatment included three levels each of N, P₂O₅, and K₂O (10, 20, and 30 g/m²). Result indicated that increased levels of nitrogen (N3) increased chlorophyll content significantly (2.47 mg/g), CSI (26.22%), and LAD (54.93 days). Phosphorus and potassium levels also had an effect on these characters, where P2 and K2 were most superior in enhancing chlorophyll content and LAD, but K3 recorded the highest CSI. Among interaction treatments, N2P1K3 had the maximum CSI (30.48%) and LAD (59.70 days), reflecting enhanced physiological efficiency and drought tolerance. The results emphasize the significance of balanced NPK fertilization to maximize growth and stress tolerance in rose culture. The findings form a platform for further optimization of nutrient management schemes to promote floricultural performance, particularly in controlled environments.